The suicide house [large type] - Donlea, Charlie (Donlea, Charlie. Rory Moore/Lane Phillips, 2021)
"Inside the walls of Indiana's elite Westmont Preparatory High School, rules are strictly enforced. But in the woods beyond the campus and playing fields sits an abandoned boarding house that is infamous among Westmont's students as a late-night hangout. One year ago, two students were killed there in a grisly slaughter. A teacher was convicted of the murders, but mysteries and questions remain. The most urgent among them is why so many students who survived that horrific night have returned -- to kill themselves. It's a dangerous game gone tragically wrong. And for its players, there may be no way to win -- or to survive." -- page [4] of cover.